PERAN KEARIFAN LOKAL DALAM MEMPERKUAT IDENTITAS MASYARAKAT TENGGER DI KABUPATEN PROBOLINGGO - Achmad Robith Khusni; Prof. Dr. Moch. Chotib, S.Ag., MM; Prof. Dr. H. Abd. Halim Soebahar, M.A; Prof. Dr. H. M. Noor Harisudin, S.Ag., S.H., M.Fil (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
The Tengger tribe is a tribe rich in culture and history. Since the Hindu Kingdom in Indonesia, the name Tengger has been known as the sacred land. The role of local wisdom that is widely unknown to the general public is a reason for researchers to review the identity of the Tengger community in particular. This research is a qualitative descriptive study that adopts an ethnographic approach that aims to describe and interpret existing cultures, social groups, and systems related to the local wisdom of the Tengger community. This study found that the role of local wisdom can be reviewed in several aspects including the value of cultural arts, customs, multicultural values, social, and the role of the Tengger community in maintaining the role of local wisdom.